Comparison of the Electrochemistry of Ni Thin Film and Ni-YSZ Composite Anodes Fabricated by Polymeric Precursor Deposition. Issue 13 (1st January 2016) - Buyukaksoy, Aligul; Birss, Viola I.
Abstract : Previous research focused on the impedance response of Ni-yttria stabilized zirconia (YSZ) solid oxide fuel cell (SOFC) anodes has provided contradictory results about the preferred equivalent circuit, the meaning of each circuit element, and the rate determining step of the H2 oxidation reaction. This has been proposed to be due to differences in the morphology of the anode layers between studies, unknown impurity concentrations related to the use of different Ni precursors, and variations in the distributed potentials within porous anode layers. Here, efforts were made to overcome these problems by comparing the impedance response of a dense, Ni thin film anode, deposited on a YSZ electrolyte pellet, with that obtained from a Ni-infiltrated porous YSZ scaffold, but using the same polymeric Ni precursor solution in both cases, thus ensuring that only the morphology of the YSZ phase differed. This revealed that the same general impedance response and the same activation energy was obtained at both anodes when the porous electrode data were fitted to an equivalent circuit that includes a transmission line element. This work thus demonstrates the importance of keeping as many parameters the same as possible in comparative model thin film and composite anode studies.